2023
DOI: 10.1037/pspp0000438
|View full text |Cite
|
Sign up to set email alerts
|

Who benefits from which activity? On the relations between personality traits, leisure activities, and well-being.

Abstract: Leisure activities have been emphasized as an important predictor of well-being. However, little research has examined the effects of leisure activity enactment on well-being over time. Moreover, it is unknown which activities are most beneficial for whom. We integrate diverse theoretical accounts of person–environment relations and propose a generic Personality–Activity–Well-Being (PAW) framework, which highlights different relations between personality traits, activities, and well-being. To investigate these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 141 publications
2
12
0
Order By: Relevance
“…Although our assessment of flourishing was not as thorough as Keyes’ measure ( Keyes, 2002 ), the population-based study that was drawn on for Keyes’ study did not have measures of diverse forms of leisure. Further, our findings are consistent with recent research that shows similar associations between diverse forms of leisure and wellbeing ( Kuper et al, 2022 ), but future research is needed to assess potentially causal associations between leisure and flourishing. We hope that the present research represents a starting point for further research on the potential links between leisure and flourishing and its important consequences for wellbeing and functioning.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Although our assessment of flourishing was not as thorough as Keyes’ measure ( Keyes, 2002 ), the population-based study that was drawn on for Keyes’ study did not have measures of diverse forms of leisure. Further, our findings are consistent with recent research that shows similar associations between diverse forms of leisure and wellbeing ( Kuper et al, 2022 ), but future research is needed to assess potentially causal associations between leisure and flourishing. We hope that the present research represents a starting point for further research on the potential links between leisure and flourishing and its important consequences for wellbeing and functioning.…”
Section: Discussionsupporting
confidence: 91%
“…It is worth noting that some of the forms of leisure we assessed (e.g., social leisure, Tables 3 , 4 ) were as strongly associated with languishing and flourishing as household income, helping to reinforce the value of leisure for health and wellbeing. We also found similar patterns to recent longitudinal research that found exercise, socializing, cultural activities and exercise were positively linked to wellbeing but computer gaming and television watching were not ( Kuper et al, 2022 ). Finally, the way we operationalized leisure participation also shows that structural approaches to assessing leisure participation have implications for subjective aspects of wellbeing.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…However, the majority of past research aiming to identify predictors of wellbeing have focused on links with subjective wellbeing only, and many have focused on cross-sectional research designs. Many longitudinal studies focus only on a single domain, such as personality 6 , lifestyle 7 , 8 , life events 9 , or leisure activities 10 separately, making it difficult to determine the degree to which these variables explain unique variance in mental wellbeing. Some longitudinal studies have been conducted which do consider multiple domains, but with a primary focus on older adults 11 13 , and the extent to which these results generalise to other stages of adulthood is unclear.…”
Section: Introductionmentioning
confidence: 99%